Respuestas
Respuesta dada por:
4
Hola.
![(5-3x)-2(-4x+6)=(8x+11)-5(3x-6)\\ \\
5-3x+8x-12=8x+11-15x+30\\ \\
-3x+8x-8x+15x=12-5+11+30\\ \\
12x=48\\ \\
x=\frac{48}{12}\\ \\
x=4 (5-3x)-2(-4x+6)=(8x+11)-5(3x-6)\\ \\
5-3x+8x-12=8x+11-15x+30\\ \\
-3x+8x-8x+15x=12-5+11+30\\ \\
12x=48\\ \\
x=\frac{48}{12}\\ \\
x=4](https://tex.z-dn.net/?f=+%285-3x%29-2%28-4x%2B6%29%3D%288x%2B11%29-5%283x-6%29%5C%5C+%5C%5C%0A5-3x%2B8x-12%3D8x%2B11-15x%2B30%5C%5C+%5C%5C%0A-3x%2B8x-8x%2B15x%3D12-5%2B11%2B30%5C%5C+%5C%5C%0A12x%3D48%5C%5C+%5C%5C%0Ax%3D%5Cfrac%7B48%7D%7B12%7D%5C%5C+%5C%5C%0Ax%3D4)
Saludos
Saludos
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años